Association between tumor-infiltrating lymphocytes and sentinel lymph node positivity in thin melanoma - Fernando De Marco dos Santos; Felipe Correa da Silva; Julia Pedron; Roque Domingos Furian; Cristina Fortes; Renan Rangel Bonamigo (Sociedade Brasileira de Dermatologia, 2019)
Abstract: Background: Sentinel lymph node biopsy in thin invasive primary cutaneous melanoma (up to 1mm thick) is a controversial subject. The presence of tumor-infiltrating lymphocytes could be a factor to be considered in the decision to perform this procedure. Objective: To evaluate the association between the presence of tumor-infiltrating lymphocytes and lymph node metastases caused by thin primary cutaneous melanoma. Methods: Cross-sectional study with 137 records of thin invasive primary cutaneous melanoma submitted to sentinel lymph node biopsy from 2003 to 2015. The clinical variables considered were age, sex and topography of the lesion. The histopathological variables assessed were: tumor-infiltrating lymphocytes, melanoma subtype, Breslow thickness, Clark levels, number of mitoses per mm2, ulceration, regression and satellitosis. Univariate analyzes and logistic regression tests were performed as well the odds ratio and statistical relevance was considered when p <0.05. Results: Among the 137 cases of thin primary cutaneous melanoma submitted to sentinel lymph node biopsy, 10 (7.3%) had metastatic involvement. Ulceration on histopathology was positively associated with the presence of metastatic lymph node, with odds ratio =12.8 (2.77-59.4 95% CI, p=0.001). The presence of moderate/marked tumor-infiltrating lymphocytes was shown to be a protective factor for the presence of metastatic lymph node, with OR=0.20 (0.05-0.72 95% CI, p=0.014). The other variables - clinical and histopathological - were not associated with the outcome. Study limitations: The relatively small number of positive sentinel lymph node biopsy may explain such an expressive association of ulceration with metastatization. Conclusions: In patients with thin invasive primary cutaneous melanoma, few or absent tumor-infiltrating lymphocytes, as well as ulceration, represent independent risk factors for lymph node metastasis.